Assessment of child's mental health problems using Strengths and Difficulties Questionnaire - Miranda George; Shweta Chandak; Milind Wasnik; Sneha Khekade; Niharika Gahlod; Harshita Shukla (Wolters Kluwer Medknow Publications, 2019)
Background: While a number of studies in the Western countries have provided estimates of prevalence for child psychiatric morbidity and associated risk factors, relatively little is known about child psychiatric problems and risk factors in developing countries like India. Aim: The aim of this study was to assess the patients' emotional status in an age group of 3-14 years to evaluate children's cooperative potential. Methodology: The Goodman's Strengths and Difficulties Questionnaire assessing the mental health status of the child was distributed to the Vidharbhan population attending the dental hospital. A cross-sectional survey including 168 children aged 3-14 years who were instructed how to fill the questions participated in the study. Results: Overall 53% of the children belonged to the normal category, whereas 33% and 14% were under abnormal and borderline categories, respectively. The abnormal category was slightly higher in the age groups of 3.1-5 (35%) and 11.1-14 (28%) years. Similar to certain studies, the mental health problems with males (52.9%) were higher than that of females (47.6%). Conclusion: Identifying the mental health problems of the child seeking dental treatment will help the dentist to formulate an idea of the child's emotional status at the time of treatment and thereby make proper amendments during the treatment procedure. There is a need for developing programs to train, sensitize, and mobilize teachers and parents regarding children's psychological, emotional, and behavioral problems, with special attention to the common population.